Immediate impact of medical abortion on women's health and clients' satisfaction with medical abortion - Paudel, N (Journal of Kathmandu Medical College, 2013)
Background: Medical abortion has been proved to be effective method for safe abortion. It is highly acceptable to women in a variety of settings, including where resources are limited. Objective: The objective of the study was to assess the immediate impact of medical abortion on women’s health and clients’ satisfaction with medical abortion.  Methods: A descriptive study was conducted at Marie Stopes Center, Satdobato, Lalitpur. A total of 100 consecutive women visiting the center for medical abortion during 2010 September to 2010 October were included. Respondents were the women attending follow up visit following medical abortion using Mifepristone 200 mg orally followed by Misoprostol 800μg per vaginal after 24 hours of oral Mifepristone. Structured questionnaire was designed and interview method was used for data collection. Statistical Package for Social Sciences version16 was used to analyze the data. Results: The success rate of medical abortion was 91%. Most of the respondents did not have any problems besides the expected effects and side effects of the method such as bleeding, abdominal cramping, nausea, vomiting, dizziness and headache. Majority (79%) of respondents was satisfied with medical abortion and 76% respondents said they would recommend this method to others in future. There was no significant relationship between information and counseling and client’s satisfaction with medical abortion. Conclusions: The immediate impact of medical abortion on women’s health is positive. It is a safe and easy method in termination of early pregnancy and most of the clients were satisfied with this method. DOI: http://dx.doi.org/10.3126/jkmc.v1i2.8144 Journal of Kathmandu Medical College, Vol. 1, No. 2, Oct.-Dec., 2012: 91-95